Peak performers : (Career Press, 2010)
In this handbook, you'll discover how to improve employee motivation through five key areas: team-building, communication, delegation, recognition, and financial incentives. You'll learn what works and what doesn't in today's volatile, ever-changing business environment. You'll explore dozens of fresh ideas, proven management techniques, and exciting new discoveries guaranteed to put your people on the fast track to peak performance.